Toxicological effects of nanoselenium in animals - Bano, Iqra; Skalickova, Sylvie; Arbab, Safia; Urbankova, Lenka; Horky, Pavel (Journal of animal science and biotechnology, 2022)
The productivity and sustainability of livestock production systems are heavily influenced by animal nutrition. To maintain homeostatic balance in the body of the animal at different phases of life, the percentage of organically active minerals in livestock feed must be optimized. Selenium (Se) is a crucial trace mineral that is required for the maintenance of many functions of the body. Se nanoparticles (SeNPs) attracted considerable interest from researchers for a variety of applications a decade ago, owing to their extraordinary properties. SeNPs offer significant advantages over larger-sized materials, by having a comparatively wider surface area, increased surface energy, and high volume. Despite its benefits, SeNP also has toxic effects, therefore safety concerns must be taken for a successful application. The toxicological effects of SeNPs in animals are characterized by weight loss, and increased mortality rate. A safe-by-strategy to certify animal, human and environmental safety will contribute to an early diagnosis of all risks associated with SeNPs. This review is aimed at describing the beneficial uses and potential toxicity of SeNPs in various animals. It will also serve as a summary of different levels of SeNPs which should be added in the feed of animals for better performance.
Keywords: Nanoparticles; Organism; Selenium; Trace minerals; Toxicity